Brief Overview About Syringoma (Journal of Pharmaceutical Negative Results, 2023)
Background: Syringomas are benign skin-adnexal tumors of eccrine origin that present as small dome-shaped papules and often occur in a periocular distribution that may compromise the facial esthetic appearance. It can also be found on the neck, abdomen, or external genitalia. The term “syringoma” comes from the Greek word syrinx, which means tube. According to their histopathological characteristics, they are benign adnexal tumors arising from the eccrine ducts. The proliferation of cells in the lumen of the duct results in the development of spiral structures in which sweat can no longer move freely or come out to the surface of the skin. Syringomas may sometimes be pruritic. Summer season or high temperature is the most common aggravating factor. The report that topical atropine is effective in the treatment of syringoma supports the hypothesis that high temperature-induced sweat secretion may worsen the symptom. Atropine is an anticholinergic drug that inhibits sweating. The most frequent clinical differential diagnosis of localized syringoma is xanthoma. This could be due to the similar localization of periocular syringoma with xanthelasma. Plane warts are the most common clinical differential diagnosis of generalized syringoma. The definite diagnosis of syringoma can be made on histopathological examination. Haematoxylin-eosin stain (H and E) shows multiple small ducts within the dermis. The ducts are lined by two rows of epithelial cells with comma-like tail or tadpole appearance